Comprehensive Assessment of Rapeseed Meal as a Fish Meal Substitute in Hybrid Sturgeon (Acipenser schrenckii ♀ × Acipenser baerii ♂) Diets: Impacts on Growth Performance, Body Composition, Immunological Responses, Intestinal Histology, and Inflammatory Response - Wenpeng Zhang; Siyuan Liu; Shidi Wang; Huamin Wang; Kaibo Ge; Yuhong Yang; Shaoxia Lu; Shicheng Han; Haibo Jiang; Chang’an Wang; Hongbai Liu (Aquaculture Nutrition)
This study aimed to assess the impact of incorporating rapeseed meal (RM) as a partial substitute for fish meal (FM) in the diet of cultured hybrid sturgeon (Acipenser schrenckii ♀ × Acipenser baerii ♂). A total of 450 juvenile hybrid sturgeon with similar weights were randomly assigned to five dietary groups, each with triplicates of 30 fish per tank. For 12 weeks, FM was replaced with varying percentages of RM (0%, 25%, 50%, 75%, and 100%). Results indicated a decreasing trend in final body weight (FBW), weight gain, and survival rates (SRs) as the ratio of RM increased. Growth performance was less affected when the substitution ratio of FM was below 50%. The replacement of FM with RM showed a decreasing trend in crude protein and ash content of sturgeon body composition and no significant effect on moisture and crude lipid content (p>0.05). Essential amino acids (EAAs) in whole fish, such as methionine (Met), threonine (Thr), and lysine (Lys), increased with higher substitution rates (p>0.05). The lysozyme (LZM) activities in the pyloric cecum, duodenum, and valve intestine of the sturgeon showed a decreasing trend (p>0.05). Nevertheless, at a 50% substitution level, sturgeon liver superoxide dismutase (SOD) and malondialdehyde (MDA) activities reached their peak. At 100% substitution, serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activities were significantly higher than in other groups (p<0.05). At 50% substitution, sturgeon valve intestinal protease activity reached its maximum, and the duodenal villus height (VH) was not significantly different from that of the control group (morphological and structural indices were lower in the treatment groups). Gene expression of pro-inflammatory factors IL-1β, IL-6, IL-8, and TNF-α increased with the substitution ratio, while anti-inflammatory factor IL-10 showed the opposite trend. NF-κB and myeloid differentiation factor 88 (MyD88) expression increased with substitution ratio, and Toll-like receptor 1 (TLR1) and Toll-like receptor 2 (TLR2) showed the opposite trend in the intestine. The results of this study suggest that replacing less than 50% of fishmeal with RM in hybrid sturgeon diets can reduce the amount of fishmeal used without compromising fish health.